DEVELOPING READING WORKSHEET BASED ON TASKBASED LANGUAGE TEACHING TO TEACH STUDENTS’ READING COMPREHENSION FOR THE TENTH GRADE STUDENTS AT SMA NEGERI 3 MEDAN - Nurhanifa Lubis; Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
The objective of this study was to develop reading worksheet based on taskbased language teaching to teach students’ reading comprehension for tenth grade students at sma negeri 3 medan. This study was conducted by using Research and Development design through six stages; gathering data and information, need analysis, materials development, validating by experts, revising, and final product. The subject of the study was the tenth-grade students in SMA Negeri 3 Medan. The data were gathered by reviewing documents, conducting an interview with the English teacher, and distributing the students' needs analysis questionnaires to X MIA 2 consists of 35 students to get the students’ needs. The interview and questionnaire results proved that the students needed reading worksheet based on task-based language teaching. The developed reading worksheets were validated by two experts which scored 3.77 and 3.87 on average. The scores approved that the reading worksheet based on task-based language teaching were very valid and suitable to use for the tenth-grade students in SMA Negeri 3 Medan. The result of the product was distributed to the students through bit.ly/TBLTworksheetKey words: Development, Reading, Worksheet, Task-Based Language Teaching.